La historieta - Padilla Colchado, Milagritos Mirella (2022)
This work is for to the students of the 2nd year of secondary school "Víctor Raúl Haya de la Torre", taking into account the virtuality as a means of teaching due to the current situation we are living focus on distance education. The purpose of this work is that students through two competences identify the different points about the comic strip such as: characteristics, elements and functions, also participate actively in the creation of a comic strip according to its context and necessary tools. Taking into consideration that a support will be provided by means of a support that will provide the teacher with the necessary information to carry out the lesson plan.